Trust Management: Key Factor of the Sustainable Organizations Embedded in Network - Jab?o?ski, Adam (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Nowadays, trust is an important determinant in the development of modern organizations. Not only is it becoming an increasingly important element of relationships between entities, but, above all, it positively influences the building of an organization's intellectual capital. This capital can be defined in different ways, but its definition always references elements that determine the potential of sustainable organizations, often in human, social, relational, organizational, and innovation dimensions. Trust is increasingly becoming the key determinant of this capital (Ko?uch, Lenart-Gansiniec, 2017). Trust also has a number of different definitions. However, the basis of many of these definitions is the building of relationships focused on developing some kind of individual or inter-organizational link. Organizational trust is a complicated concept, and it is the basis of all organized activities performed by people in the organization, largely because trust is needed to develop relationships with integrity and commitment. Thus, it is interesting to study the relationship between trust and the building of the intellectual capital of sustainable organizations. Indeed, intellectual capital plays a special role here. It is a guide and a platform for achieving not only a competitive advantage for the sustainable organization, but also a source of value creation in the short and long term. Thus, this strategic hybrid, composed of a business model, strategy, and business processes, is favorable to the development of intellectual capital (Jab?o?ski 2017). Trust is an element that ties this capital to relationships in business. Moreover, it has an integrated character (R.C. Mayer, J. H. Davis, F. D. Schoorman 1995). Assuming that, nowadays, the network paradigm is becoming increasingly important, it is worth asking how the mechanism of building trust-based intellectual capital in a sustainable organization functions as its key asset in the network environment.